Postoperative cognitive dysfunction—current research progress - Zhao, Qi; Wan, Hui; Pan, Hui; Xu, Yiquan (Frontiers in Behavioral Neuroscience, 2024)
Postoperative cognitive dysfunction (POCD) commonly occurs after surgery, particularly in elderly individuals. It is characterized by a notable decline in cognitive performance, encompassing memory, attention, coordination, orientation, verbal fluency, and executive function. This reduction in cognitive abilities contributes to extended hospital stays and heightened mortality. The prevalence of POCD can reach 40% within one week following cardiovascular surgery and remains as high as 17% three months post-surgery. Furthermore, POCD exacerbates the long-term risk of Alzheimer's disease (AD). As a result, numerous studies have been conducted to investigate the molecular mechanisms underlying POCD and potential preventive strategies. This article provides a review of the research progress on POCD.